Experiential learning implementation in tourism and adventure program at Malaysia community colleges: An in-depth exploration / Safiza Alfian Yusof - Alfian Yusof, Safiza (2023)
For the past thirty years, technical and vocational based education or training programs have been mushrooming in learning institutions. Such programs involve a lot of hands-on approach; therefore, it is often associated with experiential learning style. Experiential learning style is able to overcome the restrictions of traditional learning techniques and introduce new tools of shifting knowledge. Looking at the exciting development, this study explored the challenges and strategies to strengthen the implementation of experiential learning style from the lecturers’, industry players’ and policy makers’ perspectives. In addition, this study assessed the industry players’ perception on students’ competencies, specifically for the Tourism and Adventure program at community colleges in Malaysia. This research used a qualitative approach with constructionist research paradigm and cross-sectional time horizon approach. Face-to-face interviews were conducted with the informants at places convenient to them. A total of thirty respondents consisting of thirteen lecturers, thirteen industry players and four policy makers were interviewed. The face-to-face interview was done directly at involved community colleges and industry premises. The data gathered was transcribed verbatim and analysed for themes. Twenty main themes and forty-eight sub-themes were identified out of the three groups. For the findings, the most highlighted challenges are related to top level program management issues, followed by lecturers’ insufficient competencies and students' unfavourable attitudes for experiential learning style. As for the suggestions on new strategy for experiential learning implementation, the results suggested enhancing lecturers’ skill and knowledge, as well as more support from the top-level program management. Meanwhile the findings from industry players' perceptions on the students’ competencies indicate the students should have the ‘industry ready’ competencies. A triangulation on the themes between the three groups of respondents was also done and the result shows a pattern of concentration and connection between the findings on challenges, strategies, and perceptions on students' competencies. The findings of the study contribute to the literature on teaching and learning style using experiential learning for hospitality and tourism-based program.